Educational provisions for the deaf (lower primary level) - Victoria, Nieva Mercado 1937- (1967)
This paper presents the educational provisions for primary deaf pupils, specifically on identification and assessment of hearing loss, school programming, curriculum, and methods of instruction.
Thesis (M.A.T. Special Education)--University of the Philippines, Diliman.
Keywords: Deaf -- Education